The Effect Of The Problem-Based Learning Model On Students' Mathematical Connection Abilities And Disposition - Agnes Alfi Sirait; E Elvis Napitupulu; Zul Amry (Universitas Negeri Makassar, 2026)
The objectives of this study are to analyze: (1) the effect of Problem-Based Learning on students' mathematical connection skills; (2) the effect of the Problem-Based Learning model on students' mathematical dispositions; (3) the interaction between the learning model and KAM on students' mathematical connection skills; (4) the interaction between the learning model and KAM on students' mathematical dispositions. The population in this study consisted of all eighth-grade students at Muhammadiyah 1 Junior High School in Medan, and the sample consisted of eighth-grade students in classes VIII-2 and VIII-3, with two classes (experimental and control) comprising 60 students. The instruments used consisted of tests of students' mathematical connection abilities and scales of students' mathematical dispositions. The data were analyzed using two-way ANOVA. Based on the results of the analysis, it was found that: (1) there is an effect of the Problem-Based Learning model on students' mathematical connection skills; (2) there is an effect of the Problem-Based Learning model on students' mathematical disposition; (3) there is no interaction between the learning model and initial mathematical ability on students' mathematical connection skills; (4) there is no interaction between the learning model and initial mathematical ability on students' mathematical disposition